Forced convective tangent hyperbolic nanofluid flow subject to heat source/sink and Lorentz force over a permeable wedge: Numerical exploration - Alqahtani, Aisha M.; Bilal, Muhammad; Riaz, Muhammad Bilal; Chammam, Wathek; Shafi, Jana; Rahman, Mati ur; Adnan (Nanotechnology reviews (Berlin), 2024)
The magnetohydrodynamics tangent hyperbolic nanofluid (THNF) flow with the mutual impact of melting heat transfer and wedge angle over a permeable wedge is investigated numerically in the present study. Electronic devices generate excessive heat during operations, so THNF is often employed to regulate them. THNF has the ability to neutralize heat with greater efficacy, thereby reducing the probability of overheating. The influence of thermal radiation, Soret and Dufour, and heat source/sink is also observed on the fluid flow. The modeled equations are simplified to the lowest order through the similarity conversion. The obtained set of dimensionless equations is further calculated numerically by employing the parametric continuation method. The computational findings of the present study are compared to the published results for accuracy purposes. It has been detected that the results are precise and reputable. Moreover, from the graphical results, it has been perceived that the effect of permeability factor ( ) reduces the fluid flow. The rising effect of wedge angle factor enhances the energy dissemination rate and shearing stress; however the augmentation of Weissenberg number drops skin friction and energy transference rate.